2019
DOI: 10.1177/2333392819866620
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Antenatal Care Visit Utilization of Child-Bearing Mothers in Kaffa, Sheka, and Bench Maji Zones of SNNPR, Southwestern Ethiopia

Abstract: Background: Antenatal care (ANC) is a preventive obstetric health-care program aimed at optimizing maternal fetal outcome through regular monitoring of pregnancy. Even if World Health Organization recommends a minimum of 4 ANC visits for normal pregnancy, existing evidence from developing countries including Ethiopia indicates there are few women who utilize it due to different reasons. The purpose of this article is to identify determinants significantly influencing the ANC visit utilization of child-bearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 22 publications
6
23
2
Order By: Relevance
“…This underscores the importance of social and behavioural change communication to increase awareness and create demand for the use of maternal health services [12]. Similarly, the findings from previous studies showed that women enlightenment and early ANC initiation were significantly associated with eight or more ANC contacts [36,61]. There is no doubt, that early booking for ANC would result in optimal number of ANC contacts during pregnancy as those who start early will have higher possibility of achieving optimal ANC visits.…”
Section: Variablementioning
confidence: 78%
“…This underscores the importance of social and behavioural change communication to increase awareness and create demand for the use of maternal health services [12]. Similarly, the findings from previous studies showed that women enlightenment and early ANC initiation were significantly associated with eight or more ANC contacts [36,61]. There is no doubt, that early booking for ANC would result in optimal number of ANC contacts during pregnancy as those who start early will have higher possibility of achieving optimal ANC visits.…”
Section: Variablementioning
confidence: 78%
“…Bayou et al, also reported intention of pregnancy was found as a predictor of late ANC (13). Another study in South western Ethiopia explained, nonattendance of ANC visit was higher among women with unplanned pregnancy (14). An evidenced from South Africa and Kenya indicated, unplanned pregnancy was an independent determinant factor for late ANC (10,15).…”
Section: Discussionmentioning
confidence: 94%
“…Bayou et al, also reported intention of pregnancy was found as a predictor of late ANC (13). Another study in South western Ethiopia explained, late attendance of ANC was higher among women with unplanned pregnancy (14). An evidenced from South Africa and Kenya indicated, unplanned pregnancy was an independent determinant factor for late ANC (10,15).…”
Section: Part Ii: Determinates Of Late Anc Among Pregnant Women In Eamentioning
confidence: 93%